Qualitative analysis of the sustainability of local attachment and identity based on in-depth interviews conducted in two scattered farmstead settlements - Zoltán Bugovics (Discover Sustainability)
Abstract Based on qualitative research, the paper focuses on the transformation of the traditional lifestyle of scattered farmsteads in recent decades, primarily driven by economic shifts and demographic changes. The challenging conditions of agriculture and farming, and the rise of alternative economic activities, such as tourism, recreation, and small-scale business, have reshaped these rural settlements, contributing to a different social landscape. Besides, another important trend is the influx of newcomers, including professionals, entrepreneurs, and pensioners, who adopt alternative, often non-agricultural lifestyles while maintaining a strong sense of place attachment and identity. In contrast, younger generations of native inhabitants tend to migrate elsewhere due to limited prospects, better education and job opportunities, leading to a generational shift in the population base. This study investigates two farmstead settlements exemplifying the tendencies, highlighting how sustainability is increasingly supported not by the continuation of traditional practices, but by the emergence of new lifestyle patterns such as agritourism and rural commuting. The process of change reflects a transition in the meaning and practice of rural living, where sustainability is redefined by changing forms of identity and attachment supporting the survival of farmsteads in a postmodern world.